Positive Emotion and Honesty - Medai, Evelyn; Noussair, Charles N. (Frontiers in Psychology, 2021)
We report an experiment that considers the impact of emotional state on honesty. Using the die-rolling task created by Fischbacher and Föllmi-Heusi (2013) to detect the level of dishonesty in a sample of individuals, we study the effects of induced happiness on the incidence of self-interested lying. The experiment uses 360-degree videos to induce emotional state. We find that people behave more honestly in a state of happiness than they do in a neutral state.